Learning to teach geography in the secondary school : a companion to school experience - Lambert, David, 1932- (Routledge/Falmer, 2000)
Role, purpose and philosophy. Planning for teaching and learning in geography classrooms. Developing and using resources for teaching and learning in geography. Pupil learning in geography. Teaching geography. Valuing pupils'. Geography and education for the future. Professional development.